An acoustic investigation of intrinsic vowel duration in Danish - Bundgaard, Michael (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
The duration of twelve short and long stressed vowels in disyllabic nonsense words, embedded in a carrier sentence, recorded 10 times by each of five speakers, was measured. The vowels can be grouped (roughly) in five tongue height categories, and duration was found to increase significantly from category 1 (highest) through 5 (lowest), in about 1 cs steps. Unstressed vowels show the same tendency but the increase in duration with lower tongue height is considerably smaller. Variation in speaking rate (even rather considerable) did not significantly influence the relationship between high and low vowels. In contradistinction to earlier investigations, it seems that the difference in duration between long and short vowels is constant over different tongue heights, i.e. Vshort = Vlong – b, where b is a constant (approximately 5 cs).